Synergies of Antiangiogenic Therapy and Immune Checkpoint Blockade in Renal Cell Carcinoma: From Theoretical Background to Clinical Reality - Zhou, Xiaohan; Hou, Wanting; Gao, Ling; Shui, Lin; Yi, Cheng; Zhu, Hong (Frontiers in Oncology, 2020)
The hallmarks of renal cell carcinoma (RCC) are angiogenesis and immunogenic tumor microenvironment. Over the past decades, treatment options for metastatic RCC (mRCC) have been expanding, from the inhibition of vessel formation via antiangiogenic agents (AAs) to the stimulation of immune system by immune checkpoint inhibitors (ICIs). Since 2005, the introduction of antiangiogenic agents targeting vascular endothelial growth factor (VEGF), its receptors (VEGFRs), and mammalian target of rapamycin (mTOR) pathway have experienced moderate success in the therapeutics of mRCC, but patient outcomes remain suboptimal. Recently, the development of ICIs targeting cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and the programmed death-1/programmed death ligand 1 (PD-1/PD-L1) pathways has dramatically changed the treatment landscape of mRCC. Expressly, the combination of ipilimumab and nivolumab has been confirmed to improve clinical outcomes and approved as standard care for intermediate- or poor-risk mRCC patients. Nevertheless, innate or adaptive drug resistance is observed within both treatment approaches, limiting overall clinical benefit. This phenomenon will underscore the urgent need for new combinational therapy strategies with different mechanisms of action, which can improve efficacy in an extended patient population without severe toxic effects. In 2019, as the results of two critical phase III trials came to light, FDA approved axitinib plus avelumab or pembrolizumab as first-line standard management for mRCC, which cements the combination of AAs plus ICIs and advances the mRCC treatment field. This review summarizes current evidence on the interplay and synergetic effects between AAs and immunomodulating drugs in mRCC, focusing on the theoretical background and the status of current clinical development.